Strengthening Character Education Through Digital Literacy in Islamic Education: Evidence from Indonesia and Thailand - Ahmad Nashir; Ferdinan; Mahamadaree Waeno (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study examines how integrating digital literacy within Islamic education strengthens character education outcomes at SMP Unismuh Makassar, Indonesia, and Phatnawitya School, Thailand. A convergent mixed-methods design guided by the Stake Countenance Model was used to evaluate antecedents, transactions, and outcomes. Quantitative data were collected from 230 students through a 25-item Likert-scale survey measuring digital literacy, Islamic education mastery as a moral-cognitive outcome, and learning habits/self-regulation as a moral-behavioural outcome. Qualitative evidence was obtained from classroom observations, teacher interviews, school documents, and student reflective journals. The findings show that Makassar students scored higher on mastery (M = 85.27) and learning habits (M = 81.44) than students in Thailand (M = 77.86 and M = 74.32). Institutional context significantly affected the combined outcomes (Wilks' Lambda = 0.621, F = 52.883, p < 0.001), explaining variance in mastery (R² = 0.412) and learning habits (R² = 0.268). Digital literacy predicted both mastery (β = 0.721, p < 0.001) and learning habits/self-regulation (β = 0.387, p < 0.001). Qualitative findings indicate that digital projects supported value internalization in Indonesia, while teacher-led ethical reflection strengthened adab, tolerance, and respectful communication in Thailand. The study concludes that digital literacy can strengthen character education when it is embedded in Islamic ethical guidance, institutional policy, teacher mediation, and repeated behavioural reinforcement.